Mechanistic Insights Into Trehalose-Mediated Cold Stress Tolerance in Rapeseed (Brassica napus L.) Seedlings - Raza, Ali; Su, Wei; Jia, Ziqi; Luo, Dan; Zhang, Yi; Gao, Ang; Hussain, Muhammad Azhar; Mehmood, Sundas Saher; Cheng, Yong; Lv, Yan; Zou, Xiling (Frontiers in Plant Science, 2022)
Cold stress (CS) severely affects several physiological, biochemical, and molecular mechanisms and limits rapeseed (Brassica napus L.) growth and production. Trehalose (Tre) acts as a growth modulator, which is extensively used to improve the tolerance to multiple plant stresses. Further, Tre also serves as an external force in inducing plant signaling molecules, regulating stress-responsive genes expression, and enhancing CS tolerance in plants. Nevertheless, the importance of exogenous Tre in improving CS tolerance in rapeseed is still unclear. Therefore, the current study was designed to get mechanistic insights into Tre-mediated CS tolerance in rapeseed seedlings. To explore the Tre role, we designed four treatments [control (CK), CK + 20 mM L-1 Tre, Cold, and Cold + 20 mM L-1 Tre] and three CS conditions (4 °C, 0 °C, and -4 °C). The results showed that Tre treatments significantly mitigated adverse effects of CS on seedlings and increased the survival rate of Tre-treated seedlings under CS conditions. The exogenous Tre dramatically increased the osmoprotectants contents, including soluble sugar, soluble protein, and proline, and the activities of antioxidant enzymes such as catalase, peroxidase, superoxide dismutase, and ascorbate peroxidase were also increased under CS conditions. Additionally, Tre decreased the malondialdehyde (MDA) contents to protect the rapeseed seedlings. Moreover, Tre also remarkably augmented the expression levels of antioxidant genes (CAT12, POD34, and FSD7), CS-responsive marker genes (CBF1, CBF2, CBF4, COR6.6, COR15, COR25, COL1, and KIN1), and Tre-biosynthesis genes (TPS4, TPS8, and TPS9). Briefly, exogenous Tre not only regulates the antioxidant and osmotic balance, but it also significantly participates in Tre metabolism and signaling network to improve CS tolerance in rapeseed. Thus, Tre-induced supervisory connections between physiological or/and biochemical attributes provide information to dissect the mechanisms of Tre-mediated CS tolerance.